Decoding Viral Infection by Ribosome Profiling - Stern-Ginossar, Noam (J Virol, 2015)
Ribosome profiling is an emerging technique that uses deep sequencing to monitor translation in live cells. Studies using ribosome profiling have already provided novel insights into the identities and amounts of the proteins being produced in cells, as well as novel insights into the mechanism of protein synthesis and translation regulation. Application of ribosome profiling to cells infected with human cytomegalovirus and Kaposi's sarcoma-associated herpesvirus revealed unanticipated complexity in the coding capacity of herpesviruses. Here, I discuss these results and how the application of ribosome profiling to cells infected with other viruses can reveal novel insights into the process of infection.